Thermal comfort assessment of Plazas in Kuala Lumpur City - Ibrahim, Md. Najib; Abdul Majid, Noor Hanita (1999)
Properly designed outdoor spaces, such as plazas, may reduce the need to provide more indoor public paces. In general, indoor public spaces such as atrium, require air conditioning. Therefore, thermally comfortable outdoor spaces contribute towards energy conservation. This study provides a baseline data on thermal comfort at several plazas in Kuala Lumpur City.